Transformative Islamic Education from the Perspective KH Abdullah Munjul (Study of Manuscript Layang Siti Hasanah) - Zaimudin, Zaimudin; Ghofur, Abdul; Akbar, Meiza Fajar (Universitas Wiralodra, 2024)
The